Ovariectomy increases the phenotypic plasticity of the female prostate epithelium in the Mongolian gerbil (Meriones unguiculatus) - Zanatelli, Marianna; Custodio, Ana M. G.; Biancardi, Manoel F.; Santos, Fernanda C. A.; Góes, Rejane M. [UNESP]; Falleiros-Jr, Luiz R. [UNESP]; Vilamaior, Patricia S. L. [UNESP]; Taboga, Sebastião R. [UNESP] (CSIRO Publishing, 2017)
The female prostate is a reproductive gland that typically presents a morphology similar to that of the male gland and is highly developed in female Mongolian gerbils. Two main cell populations compose the epithelium gland: basal and secretory luminal cells. However, during postnatal development, diverse secretory cell phenotypes are distributed among the typical ones. Prostate homeostasis is under the control of sexual hormones, such as oestrogen and progesterone. After hormonal deprivation the female gland undergoes several morphophysiological changes. The objective of this study was to identify and characterise, structurally and ultrastructurally, the cellular heterogeneity of the female prostate epithelium in normal conditions and after ovariectomy. Histological routine stains, such as haematoxylin-eosin, periodic acid-Schiff and silver impregnation, as well as immunocytochemical techniques were used to enable identification of the different cell types. Some secretory cells types were identified and characterised as mucinous, basophil, clear, ciliated, droplet, spumous and neuroendocrine cells. Population tally data showed that the hormonal suppression caused by ovariectomy resulted in a decrease in the proportions of basophil and clear cells and an increase in spumous cells. Thus, the secretory epithelial cells of the female gerbil prostate are not morphologically and functionally uniform, presenting a phenotypical plasticity according to the hormonal environment in which they operate.
Keywords: cell types; electron microscopy; hormonal deprivation; immunocytochemistry; secretory cells.